Ambivalence of Gender Concept in Children's Novel: Gender Construction in "Mata di Tanah Melus" Novel by Okky Madasari - Hakdi, Asri Hakiki; Sokowati, Muria Endah (Jurnal Audiens, 2025)
Children's novels are one of the communication media that has not been studied much in Indonesia compared to research related to adolescents and adults. The contents of children's books are inseparable from the author's ideology. One of them is gender ideology, which has long been constructed in society. Mata di Tanah Melus is a semi-fantasy novel published in early 2018. This study aims to see gender construction through signs in the story. This study used Roland Barthes's semiotic analysis to obtain denotative and connotative meanings. It then forms myths. The results of this study indicate that there is an ambivalent gender construction, especially towards gender roles and gender stereotypes, that gives rise to the myth of benevolent sexism. On the one hand, women in this novel are involved in a patriarchal culture. Women have the opportunity and freedom, but they are still not free from dependence and the dominant role of men.